2015
DOI: 10.16970/ted.80131
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of leaf miner [Liriomyza cicerina Rond. (Diptera: Agromyzidae)] resistance in Cicer species

Abstract: Improvement of leaf miner [Liriomyza cicerina SummaryChickpea (Cicer arietinum L.) leaf miner [Liriomyza cicerina Rond. (Diptera: Agromyzidae)] is one of the main insect pests of chickpea since it causes substantial yield losses in Turkey. The most efficient practical, environmental and economical solutions to overcome leaf miner damage in chickpea is the utilization of resistant cultivars. The present study aims selecting resistance for leaf miner via mutation breeding in two Cicer species viz. C. arietinum L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…A susceptible commercial variety (Sierra) grown in the USA, with a unifoliolate (simple) leaf, was used as a check in field experiments. Some studies revealed that larger leaflets in chickpea were preferred by leaf miner [6,10,11]. Figure 1 shows leaves of the parents and check Sierra.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A susceptible commercial variety (Sierra) grown in the USA, with a unifoliolate (simple) leaf, was used as a check in field experiments. Some studies revealed that larger leaflets in chickpea were preferred by leaf miner [6,10,11]. Figure 1 shows leaves of the parents and check Sierra.…”
Section: Plant Materialsmentioning
confidence: 99%
“…were found [9,10]. Some mutant Cicer lines were reported to be resistant to leaf miner [6,[10][11][12]. Resistant cultivars can be bred by inter-and intra-specific crosses and mutation breeding.…”
Section: Introductionmentioning
confidence: 99%
“…While resistance to O. crenata is relatively common in chickpea, O. foetida causes significant damage in chickpea, notably in Tunisia, where research programmes aim to improve resistance to O. foetida through symbiotic rhizobia and radiation‐induced mutagenesis . Indeed, mutagenesis through chemical or physical treatments is a well‐known method used with success in plant breeding for increasing genetic diversity, notably in crops with restricted genetic variability . Concerning resistance to broomrape, interest in chemicals and gamma radiation was demonstrated for sunflower and tomato challenged with O. cumana and P. ramosa respectively …”
Section: Introductionmentioning
confidence: 99%
“…Of the 14 different accessions evaluated in the present study, AWC 612 and AWC 612M are of C. reticulatum and the remaining 12 (Sierra, CA 2969, ICC 6119, ICC 4951, FLIP 2005‐1C, FLIP 2005‐7C, LMR 60, LMR 154, ILC 3397, YAR, ACC 3305 and ACC 5305) are cultivated chickpea accessions. ACC 3305 and ACC 5305 were previously selected as mutant lines based on their morphological appearance after gamma ray treatment of their parental lines, ICC 6119 and ICC 4951, respectively (Ikten et al, 2015). Other lines, ICC 6119 and LMR 154, have multipinnate leaves, while AWC 612, ILC 3397, FLIP 2005‐1C, FLIP 2005‐7C, LMR 60, CA 2969, YAR, and ICC 4951 have fern, or normal, leaves.…”
Section: Methodsmentioning
confidence: 99%
“…Other lines, ICC 6119 and LMR 154, have multipinnate leaves, while AWC 612, ILC 3397, FLIP 2005‐1C, FLIP 2005‐7C, LMR 60, CA 2969, YAR, and ICC 4951 have fern, or normal, leaves. Sierra, ACC 5305, and ACC 3305 have simple leaves (Toker et al, 2012; Ikten et al, 2015). Improved lines (FLIP and LMR) from ICARDA were screened for resistance to leaf miner over 5 yr from 2011 to 2016, while mutants (ACC lines) were screened for 9 yr from 2007 to 2015.…”
Section: Methodsmentioning
confidence: 99%